Senegal: ClimBeR Inception Workshop Report - Rose, Sabrina; Valencia, Lina; Chabot, Philippe; Ouédraogo, Issa (CGIAR System Organization, 2022)
The CGIAR Initiative on Climate Resilience, ClimBeR, aims to transform the climate adaptation capacity of food, land, and water systems in Senegal and five other countries (Kenya, Zambia, Morocco, Philippines, Guatemala), ultimately increasing the resilience of smallholder production systems to withstand severe climate change effects like drought, flooding, and high temperatures. In Senegal, the main production sectors (agriculture, livestock and fisheries, etc.) are affected by climate change and variability. The reduction in the period of biomass growth, the irregular distribution of rainfall in time and space, increasing land degradation and the frequency of dry periods and floods have all contributed to the decline in agricultural and animal productivity. If left unchecked, climate change could jeopardize the efforts developed and initiatives put in place by the Government of Senegal to achieve economic growth and emergence as set out in its Emerging Senegal Plan (Plan Sénégal Emergent, PSE). The adoption of adaptation measures to combat the effects of climate change has therefore become a priority for the Government of Senegal and its development and research partners. ClimBeR in collaboration with the Senegal’s Ministry of Environment and Sustainable Development (MEDD) and the National Agency of Civil Aviation and Meteorology (ANACIM) organized a workshop on 19 July 2022 to bring together stakeholders to deepen understanding on how to co-generate innovations that can contribute to build systemic resilience against climate variability and extremes in Senegal. The main objective of the workshop was to develop a common vision and an action plan on how to strengthen climate adaptation efforts in Senegal. About 43 organizations in Senegal were represented in this meeting at the Radisson Blu Hotel. We had in total 110 participants in person and at least five participants online. (Please refer to Annex 1 for a detailed list of organizations).